Pengaruh Metode Menulis Berantai terhadap Keterampilan Menulis Puisi pada Siswa Kelas X SMA Negeri 4 Binjai - Maria Sihombing; Inayah Hanum (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2024)
This study is motivated by the low skill of writing student poetry which is influenced by several factors. This study aims to influence the use of chain writing method on the poetry writing skills of X grade students of SMA N 4 Binjai. The method used in this research is experimental method with two group posttest only design. The population in this study were all X grade students of SMA Negeri 4 Binjai totaling 110 people and the samples in this study were X IPA 3 students as the experimental class with 35 students and X IPA 2 as the control class with 36 students. The data analysis technique used in this study is quantitative data by testing the requirements of analysis, homogeneity test, homegenity test and hypothesis testing. The results of the study in the experimental class obtained an average value of 79.57 in the good category, while the results of the study in the control class at an average value of 47.91 were in the very poor category. Based on the similarity test of the average value, it is known that the experimental class is greater in value than the control class with a difference of 31.66%. Based on the results of the t test that has been carried out, the value obtained at a significant level a = 0.05 is obtained the value of the t table provision of 2.03 and the tcount = 13.58. Therefore, tcount ˃ ttable is 13.58 > 2.03, so ho (null hypothesis) is rejected and ha (alternative hypothesis) is accepted. Overall, it can be concluded that teaching using the chain writing method has a positive effect on the results of students' poetry writing skills in class X SMA Negeri 4 Binjai.